The Influence of A Conducive Educational Environment on Students Interest in School Attendance at Madrasah - Tirta Harnita; Maharani Maharani (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
: Student interest in attending school is important in supporting educational success, but in practice, many students still show a lack of motivation to attend and actively participate in school. One factor that is thought to influence this interest is the school environment. This study aims to determine the influence of the school environment on student interest in attending school at Madrasah Tsanawiyah Wangi-Wangi Selatan, Wakatobi Regency. The school environment is an important external factor that can shape learning interest and support educational success. This study uses a quantitative approach with a correlation method. The sample consisted of 54 students selected through proportional random sampling. The instrument used was a Likert scale questionnaire that had been tested for validity and reliability. The results of the analysis showed that the school environment had a significant influence on students' interest in attending school. Based on the categorization of scores, the school environment was in the influential category with the largest proportion of 37%, while interest in attending school was in the moderately influential category with a proportion of 46%. The F-test revealed a positive and significant relationship, with Fcount = 17.149 > Ftable = 4.02 and significance 0.000 < 0.05. Thus, the school environment was proven to play an important role in increasing students' interest in attending school. https://lamargaritacosalem.com/menu/ https://www.catiriartoasis.com/jewelry.html